Comparative Analysis of the Complete Chloroplast Genomes of Five Quercus Species - Yang, Yanci; Zhou, Tao; Duan, Dong; Yang, Jia; Feng, Li; Zhao, Guifang (Frontiers in Plant Science, 2016)
Quercus is considered as one of the most important genera in the Northern Hemisphere as its economic and ecological importance. Oaks are taxonomically perplexing due to interspecific shared morphological traits and intraspecific morphological variation, which mainly attributed to hybridization. Universal plastid markers could not provide sufficient variable sites to explore the phylogeny of this genus and chloroplast genome-scale data proved to be useful to resolve intractable phylogenetic relationships. In this study, four complete chloroplast genomes of Quercus species were sequenced and one published chloroplast genomes of Q. baronii was retrieved for comparative analyses. The sizes of these five chloroplast genomes ranged from 161,072 bp (Q. baronii) to 161,237 bp (Q. dolicholepis), which has been identified the gene organization, gene order and GC content are similar to other published Fagaceae species. We analyzed the nucleotide substitution, indels and repeats in chloroplast genomes. The detection of 19 relatively highly variable regions provides potential plastid markers for further taxonomic and phylogenetic study within Quercus. We future observed that 4 genes (ndhA, ndhK, petA and ycf1) were subjected to positive selection. Finally, the phylogenetic relationships of the published Quercus species inferred from chloroplast genomes obtained moderate-to-high supports, indicating that chloroplast genome data may be useful to resolve the relationships of this genus.